2010
DOI: 10.1111/j.1750-3841.2009.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes and Microbial Storage Stability of Caviar from Cultivated White Sturgeon (Acipenser transmontanus)

Abstract: Caviar was prepared from white sturgeon (Acipenser transmontanus) roe by adjusting the water phase salt (WPS) to 4.0% to 6.3% by adding food grade NaCl. Fish were obtained from 2 different farms from the Inland Northwest (N = 5). Salt was absorbed at a different rate and to a different extent by roe from different fish. The lipid content in the fish roe varied from 10.2% to 14.4% (w/w), with palmitic acid and oleic acid being the most abundant saturated and monounsaturated fatty acids present, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…; Shin et al . ). Farmed caviar from intensive aquaculture significantly differs from that of wild origin, while composition of extensively farmed caviar does not largely differ from wild caviar (Gessner et al .…”
Section: Caviar and Aquaculture: The Bright Side Of The Moonmentioning
confidence: 97%
See 1 more Smart Citation
“…; Shin et al . ). Farmed caviar from intensive aquaculture significantly differs from that of wild origin, while composition of extensively farmed caviar does not largely differ from wild caviar (Gessner et al .…”
Section: Caviar and Aquaculture: The Bright Side Of The Moonmentioning
confidence: 97%
“…Borax use is prohibited in the USA (Shin et al . ). Currently, only few preservatives can be used, while physical treatments are not suitable for caviar conservation (Table ).…”
Section: Caviar and Aquaculture: The Bright Side Of The Moonmentioning
confidence: 97%
“…Certain countries permit the addition of borax for preservation and to impart sweetness but this is prohibited in the US (Bledsoe et al, 2003;Shin et al, 2010).…”
Section: Fish Roe Processingmentioning
confidence: 99%
“…In order to increase its shelf life, many methods like low‐temperature storage, salting, smoking, drying, or marinating have been used during the storage process. Many studies reported quality changes of caviar during storage, such as comparison of fresh and dried caviar by means of proximate composition and quality changes during storage at 4 ± 2°C (Çelik, Altınelataman, Dinçer, & Acarlı, ), psycrotrophic bacteria in Persian sturgeon caviar (Safari & Yosefian, ), quality attributes, and microbial storage stability of caviar from cultivated white sturgeon (Shin, Oliveira, & Rasco, ), microbial risk assessment of Persian caviar during processing and cold storage (Razavilar & Rezvani, ), and chemical and sensorial changes in rainbow trout caviar salted in different ratios (İnanli, Coban, & Dartay, ). The monitoring and analysis of the quality changes are essential during the period of caviar processing and storage.…”
Section: Introductionmentioning
confidence: 99%